Tropical orchid mycorrhizae: potential applications in orchid conservation, commercialization, and beyond - Tupac Otero, Joel; Mosquera, Ana Teresa; Flanagan, Nicola S. (Lankesteriana: International Journal on Orchidology, 2013)
Orchid mycorrhizae are unique interactions in the plant kingdom involving all the orchids and a variety of fungi including Rhizoctonia. Orchids are one of the most charismatic plant families and include at least 20,000 species widely appreciated by specialist growers and scientists. They also include Vanilla, source of one of the most traded spices worldwide. Most mycorrhizal fungi belong to a group of basidiomycetes widely known for their pathogenic interaction with many crop plants including potatoes, rice, and beans. The main application of orchid mycorrhizal fungi is in the propagation of endangered and commercial orchid species, but we have recently documented an alternative use. The fungal symbionts of orchids have the ability to induce resistance to Rhizoctonia in rice plants, which opens new possibilities of biological control agents never previously imagined.